2006
DOI: 10.1051/forest:2006013
|View full text |Cite
|
Sign up to set email alerts
|

Sapwood hydraulic recovery following thinning in lodgepole pine

Abstract: -Sapflow in lodgepole pine (Pinus contorta) was measured over the summer of 2002 to assess the impact of reduced sapwood permeability (k) after thinning on tree water use. Lodgepole pine in recently thinned (RT), thinned five years prior (5T), and un-thinned (C) stands were instrumented with thermal dissipation sap flow sensors. Daily water use varied considerably (10.8-0.04 L Day −1 ), but trees in the thinned areas used more water. Despite lower k and leaf specific hydraulic capacity (Q L ) in both RT and 5T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Stand transpiration of the thinned plot exceeded that in the reference plot from 4 July, except for a few days in October 1999, though the difference was only significant during the drought periods. Similar results were found for lodgepole pine (P. contorta) where the leaf area based transpiration increased from 80 to 200% of the reference during the first 3 months after thinning (Reid et al, 2006). In a loblolly pine (P. taeda) thinning experiment, the 50 and 75% removals of BA resulted in reductions of 29 and 43%, respectively, in stand transpiration, compared to the reference, during the first wet growing season.…”
Section: Recovery After the Thinning In 1999supporting
confidence: 83%
“…Stand transpiration of the thinned plot exceeded that in the reference plot from 4 July, except for a few days in October 1999, though the difference was only significant during the drought periods. Similar results were found for lodgepole pine (P. contorta) where the leaf area based transpiration increased from 80 to 200% of the reference during the first 3 months after thinning (Reid et al, 2006). In a loblolly pine (P. taeda) thinning experiment, the 50 and 75% removals of BA resulted in reductions of 29 and 43%, respectively, in stand transpiration, compared to the reference, during the first wet growing season.…”
Section: Recovery After the Thinning In 1999supporting
confidence: 83%
“…Previous studies in forests of Oak (Bréda et al, ) and Lodgepole pine (Reid et al . , ) have found that forest thinning results in greater soil moisture availability and can lead to a higher rate of transpiration among the remaining trees. Without a paired study of a thinned and unthinned plot at our forest, it was not possible to directly conclude that thinning allowed greater soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the remaining trees are exposed to greater radiation and wind loading, which can lead to water stress (Reid et al . , ). Ma, Concilio, Oakley, North, and Chen () found that the net effect of thinning upon soil moisture was positive across six thinning treatments of mixed‐conifer stands, when basal area was reduced by 12.4–66.0%.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The upper probe was continuously heated to constant power by the Joule effect whereas the lower one was not heated, remaining at trunk temperature (reference probe). In spite of some technical weaknesses (Köstner et al 1998), this method is one of the most widely used in ecophysiological research (Delzon et al 2004;Ford et al 2004;Reid et al 2006). When sap moves upwards, the temperature difference between heated and unheated probes decreases.…”
Section: Sap Flow Monitoringmentioning
confidence: 98%